PENGARUH TAYANGAN KULTUM DI RCTI TERHADAP MINAT MENONTON MASYARAKAT - Prasetyo Adinugroho (Universitas Pakuan, 2021)
AbstractTelevision is a place for people to get entertainment and information that is new and fast. With television, people can also communicate directly and get interesting entertainment. Program shows on private TV stations of various kinds, there are news programs, documentaries, features, soap operas, music. The variety of the program, aims to make the public interested to watch the program that aired. Not only that, all programs aired by TV stations aim to provide information and entertainment to the public. This study aims to find out how much Influence of Impressions